GDF15 promotes simultaneous astrocyte remodeling and tight junction strengthening at the blood–brain barrier. Issue 7 (13th March 2020) - Malik, Victoria A.; Zajicek, Franziska; Mittmann, Laura A.; Klaus, Johannes; Unterseer, Sandra; Rajkumar, Sandeep; Pütz, Benno; Deussing, Jan M.; Neumann, Inga D.; Rupprecht, Rainer; Di Benedetto, Barbara
Abstract: Perivascular astrocyte processes (PAP) surround cerebral endothelial cells (ECs) and modulate the strengthening of tight junctions to influence blood–brain barrier (BBB) permeability. Morphologically altered astrocytes may affect barrier properties and trigger the onset of brain pathologies. However, astrocyte‐dependent mediators of these events remain poorly studied. Here, we show a pharmacologically driven elevated expression and release of growth/differentiation factor 15 (GDF15) in rat primary astrocytes and cerebral PAP. GDF15 has been shown to possess trophic properties for motor neurons, prompting us to hypothesize similar effects on astrocytes. Indeed, its increased expression and release occurred simultaneously to morphological changes of astrocytes in vitro and PAP, suggesting modulatory effects of GDF15 on these cells, but also neighboring EC. Administration of recombinant GDF15 was sufficient to promote astrocyte remodeling and enhance barrier properties between ECs in vitro, whereas its pharmacogenetic abrogation prevented these effects. We validated our findings in male high anxiety‐related behavior rats, an animal model of depressive‐like behavior, with shrunk PAP associated with reduced expression of the junctional protein claudin‐5, which were both restored by a pharmacologically induced increase in GDF15 expression. Thus, we identified GDF15 as an astrocyte‐derived trigger of astrocyte process remodeling linked to enhanced tight junction strengthening at the BBB. Abstract : Perivascular astrocyte processes (PAP, astrocyte endfeet) produce growth/differentiation factor 15 (GDF15), which is released and modulates the astrocyte morphological changes and tight junction strengthening. Astrocytes and tight junctions are disrupted in diseased conditions and can be restored by pharmacologically driven increased GDF15 production at PAP.